A categorical recall strategy does not explain animacy effects in episodic memory. Issue 4 (3rd April 2017) - VanArsdall, Joshua E.; Nairne, James S.; Pandeirada, Josefa N. S.; Cogdill, Mindi
ABSTRACT: Animate stimuli are better remembered than matched inanimate stimuli in free recall. Three experiments tested the hypothesis that animacy advantages are due to a more efficient use of a categorical retrieval cue. Experiment 1 developed an "embedded list" procedure that was designed to disrupt participants' ability to perceive category structure at encoding; a strong animacy effect remained. Experiments 2 and 3 employed animate and inanimate word lists consisting of tightly constrained categories (four-footed animals and furniture). Experiment 2 failed to find an animacy advantage when the categorical structure was readily apparent, but the advantage returned in Experiment 3 when the embedded list procedure was employed using the same target words. These results provide strong evidence against an organizational account of the animacy effect, indicating that the animacy effect in episodic memory is probably due to item-specific factors related to animacy.